Cover Crop Impacts on Soil Water Status - M. Kuykendall; K. Roozeboom; G. J. Kluitenberg; P. V. Vara Prasad (Kansas Agricultural Experiment Station Research Reports, 2015)
Water is a primary concern for producers in the Great Plains; as such, research is warranted to quantify how much cover crops affect the amount of soil water available to subsequent cash crops. Cover crop mixes have been marketed as a means to conserve water in no-till cropping systems following winter wheat (Triticum aestivumL.) harvest. The objectives of this study are to quantify changes in soil profile water content in the presence of different cover crops and mixtures of increasing species complexity, to quantify their biomass productivity and quality, and to quantify the impact of cover crops on subsequent corn (Zea maysL.) yields. We hypothesized the change in soil water brought on by the cover crop treatments would be correlated to the quantity of biomass produced and the species composition, rather than mixture complexity. Soil moisture was measured using a neutron probe to a depth of 9 ft. Results from 2013–14 showed no difference in water use between cover crop mixtures and single species. Cover crops depleted the soil profile by a maximum of 3.5 in. during growth, but fallow was able to gain 0.75 in. of water during the same period. At the time of corn planting, soil moisture under all cover crops had replenished to levels at cover crop emergence, except for the brassicas, which had extracted water from deeper in the profile. Corn yields were reduced following the grass cover crops and the six-species mix. Corn yields were more closely related to the carbon:nitrogen (C:N) ratio of the cover crop residue than to profile soil moisture at corn emergence. The fact that yields were similar for corn after fallow and for corn after brassica cover crops implied that water was not the cause of yield reductions after the other cover crops.
Keywords: cover crops; soil water; fallow; corn